CONTENT MARKETING STRATEGIES AND BUILDING BRAND AWARENESS IN THE ERA OF SOCIAL MEDIA: A PHENOMENOLOGICAL STUDY ON INDONESIAN MSMES - Dumarya Manik, Cornelia (Yayasan Education and Social Center, 2025)
This study aims to explore the experiences of Indonesian MSMEs (Micro, Small, and Medium Enterprises) actors in implementing content marketing strategies and building brand awareness in the social media era. Digital transformation has created strategic opportunities for MSMEs to reach broader markets, yet its implementation still faces complex challenges related to digital literacy, resource constraints, and platform algorithm dynamics. This research employs a qualitative approach with transcendental phenomenology method involving 20 informants from various business sectors and geographical regions in Indonesia. Data collection was conducted through semi-structured in-depth interviews, participant observation of social media activities, and document analysis of marketing content. Data analysis utilized the Colaizzi method while adhering to Lincoln and Guba's trustworthiness criteria to ensure data validity. The research identified six main themes: (1) evolution of content marketing understanding from transactional to relational, (2) creative strategies in content creation based on storytelling and format diversification, (3) challenges in content consistency and management due to time and technical skill limitations, (4) importance of active interaction and engagement with audiences to build brand communities, (5) adaptation to algorithm changes and social media platform trends, and (6) success measurement and continuous learning. Findings indicate that success in building brand awareness is not determined by formal educational background or business scale, but rather by creativity, consistency, adaptability, and deep understanding of audience characteristics. Effective strategies include authentic storytelling based on brand values, collaboration with micro-influencers, utilization of user-generated content, and development of loyal brand communities. This research contributes theoretically to the development of contextual content marketing models for MSMEs in developing countries and provides practical implications for MSME actors, policy makers, educational institutions, and digital platform providers. Research limitations lie in the geographical focus on urban and semi-urban areas, thus future research is recommended to explore MSME experiences in remote areas and conduct longitudinal studies to understand the evolution of content marketing strategies in the long term.